-(8+4n)=-6(3n-1)

Simple and best practice solution for -(8+4n)=-6(3n-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(8+4n)=-6(3n-1) equation:


Simplifying
-1(8 + 4n) = -6(3n + -1)
(8 * -1 + 4n * -1) = -6(3n + -1)
(-8 + -4n) = -6(3n + -1)

Reorder the terms:
-8 + -4n = -6(-1 + 3n)
-8 + -4n = (-1 * -6 + 3n * -6)
-8 + -4n = (6 + -18n)

Solving
-8 + -4n = 6 + -18n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '18n' to each side of the equation.
-8 + -4n + 18n = 6 + -18n + 18n

Combine like terms: -4n + 18n = 14n
-8 + 14n = 6 + -18n + 18n

Combine like terms: -18n + 18n = 0
-8 + 14n = 6 + 0
-8 + 14n = 6

Add '8' to each side of the equation.
-8 + 8 + 14n = 6 + 8

Combine like terms: -8 + 8 = 0
0 + 14n = 6 + 8
14n = 6 + 8

Combine like terms: 6 + 8 = 14
14n = 14

Divide each side by '14'.
n = 1

Simplifying
n = 1

See similar equations:

| x+3x=8(x-3)+2(x+3) | | 2x+2=1X-5 | | 3y^2-36y+9=0 | | 8x+2=10x-6 | | 4=3x+2(-2x-3) | | 3y^2-6(6y-3/2)+6=0 | | 4/3+2/3x=13/6+3/2x+1/2 | | X^2+y^2=19 | | (x^2+2)/(x-2)=3x/(x-2) | | HR=0.8(220-14) | | x^2+2/x-2=3x/x-2 | | -2(5v-3)+8=-4(1+4v) | | 28(5/7x+1/4) | | 8a+41=185 | | 25(5/7x+1/4) | | 10-(2z-8)=1-3z | | 76=-5x+3(-3+2) | | x+3.2x=6.6 | | 20x^3-21x^2=0 | | -1=7x-3(2x+4) | | 5(-2x+5)=-35 | | 7+4m-3=9m+8-4m | | 6(9+3x)=162 | | N+8=-7h+8 | | 5+8=678 | | 7(4x+3)=287 | | 8(5n+4)=8(1+2n) | | 7n+15n=176 | | 3x+x+(x-2)=110 | | 4x^2-18x-6=0 | | 4x+6=39-7x | | x/10=-29 |

Equations solver categories